Electronic structure properties of boron–doped and carbon–boron–codoped TiO2(B) for photocatalytic applications. (June 2022) - Heffner, Herman; Faccio, Ricardo; López-Corral, Ignacio
Abstract: A path to enhance the efficiency of photocatalytic devices is by doping the active semiconductor in order to maximize the light absorption. However, impurities could increase the recombination of photoinduced charge carriers, in order that a careful analysis on the effects of those impurities it is necessary. On this research, density functional theory calculations were applied to analyze the structure and electronic characteristics of B–doped and C+B–codoped TiO2 (B) considering the lowest formation energy of substitutional impurities. Our calculations suggest that the swapping of a boron or carbon atom for an oxygen atom (B@O or C@O) is energetically more favorable than the replacement of titanium atoms. The obtained results seem to indicate that the boron substitution into O2C and O3C1 sites leads to its migration towards interstitial sites in both mono and codoping, thus causing a great geometrical distortion compared to pure TiO2 (B). Furthermore, impurity states in the band gap were obtained after B@O doping and C+B–codoping, producing an improvement of the optical properties, so it can be assumed that this nanomaterial might act as a photoelectrode after an adequate design optimization that facilitates the charge carrier separation. Graphical abstract: Image 1 Highlights: DFT + U models suggest B and C + B–doping on TiO2 (B) are more favorable at O-sites. The boron dopant occupies preferentially near interstitial sites. DOS analysis shows C + B–doping can originate a reduction of the band gap. Impurity midgap levels are developed after doping, which may enhance optical properties. Results suggest C + B–doping of TiO2 (B) could improve efficiencies of photosensitive devices.